Peran Safety Management System dalam Keselamatan Pelayaran - Ali Sumara El Khomeiny; Falldy Primanta; Sjahrial Nasution (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
SMS is an important thing that is owned by all PT Hafar Daya Samudera's fleet. The main problems and objectives in this thesis are how is the implementation of the SMS (Safety Management System) to Neptune's Hafar Barge, how are the security and safety shipping procedures implemented by the crew at the time of emergency and are there any influence of the safety management system and the shipping safety on Barge Hafar Neptune on PT Hafar Daya Samudera. The results of the calculation of data processing by the author is important for Barge Hafar Neptune to implement a safety management system proven by the weight and average results of research calculations of 92 (4.60). It is important for companies to carry out accident prevention related to the safety management system according to the calculation and data processing carried out by the authors. The highest weight and average percentage according to the results of research calculations is 124 (6.20) and it is important for the company to improve accident prevention on Barge Hafar Neptune which is proven by the weight and average results of research calculations of 96 (4.80).